Boosting Zn-ion storage performance of bronze-type VO2 via Ni-mediated electronic structure engineering - Cai, Yi (2021)
Aqueous rechargeable zinc-ion batteries are emerging as attractive alternatives for post-lithium-ion batteries. However, their electrochemical performances are restricted by the narrow working window of materials in aqueous electrolytes. Herein, a Ni-mediated VO2–B nanobelt [(Ni)VO2] has been designed to optimize the intrinsic electronic structure of VO2–B and thus achieve much more enhanced zinc-ion storage. Specifically, the Zn/(Ni)VO2 battery yields a good rate capability (182.0 mA h g–1 at 5 A g–1) with a superior cycling stability (130.6 mA h g–1 at 10 A g–1 after 2000 cycles). Experimental and theoretical methods reveal that the introduction of Ni2+ in the VO2 tunnel structure can effectively provide high surface reactivity and improve the intrinsic electronic configurations, thus resulting in good kinetics. Furthermore, H+ and Zn2+ cointercalation processes are determined via in situ X-ray diffraction and supported by ex situ characterizations. Additionally, quasi-solid-state Zn/(Ni)VO2 soft-packaged batteries are assembled and provide flexibility in battery design for practical applications. The results provide insights into the interrelationships between the intrinsic electronic structure of the cathode and the overall electrochemical performance.